Literature Review : Peran Kelengkapan Sumber Daya Manusia (SDM) Keselamatan Dan Kesehatan Kerja (K3) Dalam Meningkatkan Efektivitas Sistem Manajemen Keselamatan Pertambangan (SMKP) Risiko: Kelengkapan Sumber Daya Manusia (SDM) Keselamatan Dan Kesehatan Kerja (K3) - Dwi Retno Apriani Putri; Devanda Faiqh Albyn (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
Background: The mining sector worldwide, including Indonesia, is one of the industries with the highest risk of occupational accidents and diseases (OIDs) (ILO, 2023). Methods: In this study, researchers limited the study to 17 journal articles deemed most relevant and eligible for further analysis as a basis for discussion. This limitation was established to maintain the focus of the analysis and depth of synthesis in answering the previously formulated research questions. Urgency: This research will be conducted to address the operational complexity, high risks, and knowledge gaps that still exist in the mining sector. Through a synthesis of the latest scientific evidence, this study aims to identify patterns, best practices, and challenges in implementing OHS HR in SMKP. Objective: To identify patterns, best practices, and challenges in implementing OHS HR in SMKP. Significant expected contributions include: (1) developing more effective, evidence-based OHS policies, (2) developing targeted and relevant OHS HR training and competency development programs tailored to industry needs, (3) improving company OHS management practices, particularly in optimizing the role of OHS HR, and (4) improving worker safety and well-being by reducing the number of accidents and occupational diseases in the mining environment. Conclusion: Implementation of the OHS Management System (SMK3), Technology Integration in OHS Management, Evaluation of OHS Management and Financial Performance, Gaps in the Quality and Quantity of OHS HR, and the Role of OHS HR in the Implementation of the SMKP.